Equality and fairytales. Action research in a preschool - Hreiðarsdóttir, Anna Elísa (Menntavísindasvið Háskóla Íslands, 2018)
This article describes action research intended to monitor a developmental project on gender equality and fairy tales in a preschool in Akureyri. The project was conducted in the school year 2013-2014. The author took part in the study, as project manager, along with the teachers. The Ministry of Education, Science and Culture sponsored the project through the Venture Fund for Preschools, Primary and upper Secondary Schools. According to the Icelandic National Curriculum for Preschools, equality is one of the fundamental pillars of education and, as the curriculum states: “critical examination is an important part of equality education, for example because established ideas in the society influence ideas and views and therefore it is critical to teach young children to voice and analyse the circumstances that lead to discrimination of some and privileges for others” (Aðalnámskrá leikskóla, 2011). It is clear that schools are supposed to work on and teach equality but in reality, studies show both those aspects to be lacking (Eygló Árnadóttir, 2009; Þorgerður Einarsdóttir & Ingólfur Ásgeir Jó-hannesson, 2011). One reason could be a shortage of teaching materials, especially in gender equality. Therefore, it is important to work towards equality in schools and it is of particular significance to develop educational material for teachers. The main purpose of the developmental project was to increase teachers’ knowledge of gender education and to develop methods in equality and gender teaching, as well as work-ing on, and improving, preschool children’s gender awareness, and finding ways to develop equality and gender education in preschools. The goal of the action research was to empower the teachers as professionals and further their skills to develop their own teaching methods by systematically paying attention to the project and revising it, especially the participation of the children and their contribution. The participants consisted of a classroom of 4 year olds and their teachers. Data was gathered ...